Industry and Social Change in Majalengka - Hendra Mulyadi; Efan Saeful Anam; Supriyadi; Firly Ayu Kusumawardani; Bambang Yuniarto (Formosa Journal of Social Sciences (FJSS), 2023)
Industry is one of the sectors that has an important role in the social and economic development of a region. Thisresearch aims to explore and analyze the relationship between industry and social change in Majalengka. This research uses qualitative methods with a descriptive approach to analysis. The source of data in this study is in the form of writing, both observations, actions, and additional data such as documents and profiles of Majalengka. The results showed that industrial interest was marked by the shift of several factories or companies in the Karawang, Cikarang and Bexpansion areas. Fenomena underlies the basis for the shift in social behavior of the people of Majalengka district along with the development of industry in the area